PENGARUH GAYA KEPEMIMPINAN, BUDAYA ORGANISASI, UKURAN, UMUR DAN KEPEMILIKAN PERUSAHAAN TERHADAP KEPATUHAN KEWAJIBAN PAJAK - Dhaniel Hutagalung; Waluyo Waluyo (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2014)
This study aims to: (1) determine and predict the relationship leadership style influence on tax compliance, (2) determine the influence of organizational culture on tax compliance, (3) determine the effect of firm size on tax compliance, (4) determine the effect of age corporate tax compliance, and (5) the effect of ownership on tax compliance.Associative and quantitative statistical methods are used. Object and the sample are property, real estate and construction company sector in Jakarta, and are listed on the Indonesian Stock Exchange. The sampling technique used by census method based on the number of small population. 32 respondents of tax staff / manager, accounting or finance were used as the primary data. Spread questionnaires were analyzed using Structural Equation Modeling (SEM) with an alternative Partial Least Square (PLS) using SmartPLS program version 2.0 M3. SEM-PLS is used because of the difference in scale of measurement variables and lack of samples.The results showed that of the five hypotheses proposed, only two hypotheses are acceptable. Organizational culture has an significant influence and firm size variabel affect tax compliance by 17.79% and significant with T-statistic of 2.41 (>1,96). The larger the company the more it is likely to dutifully carry out their tax compliance and predictions on the role of leadership styles to improve tax compliance is acceptable. Leadership style affect by 19,91% and no significant with T-Statistic 1.83 (<1.96) at 5% significance level, age and ownership of the company was found do not affect the Tax compliance. R-square showed value of 0.4003 indicates, the relationship model are moderate which means that all variables affect the overall 40.03% of the tax compliance.